The usefulness of pretreatment controlling nutritional status score for predicting recurrence in patients with esophageal squamous cell carcinoma undergoing neoadjuvant immunochemotherapy: A real-world study - Feng, Jifeng; Wang, Liang; Yang, Xun; Chen, Qixun; Cheng, Xiangdong (Frontiers in Immunology, 2022)
Background The controlling nutritional status (CONUT) score, as an immune-nutritional index, has been reported to be related to prognosis in several cancers. Neoadjuvant immunochemotherapy (nICT) is an emerging pattern for cancer treatment in recent years. However, the usefulness of CONUT in esophageal squamous cell carcinoma (ESCC) with nICT has not been reported so far. This study attempted to clarify the usefulness of CONUT in predicting disease-free survival (DFS) in ESCC with nICT. Methods Two hundred sixteen ESCC patients receiving nICT between 2019 and 2021 were retrospectively enrolled. Based on CONUT, the patients were divided into two groups: low groups (score ≤ 2) and high (score ≥ 3) groups. The relationships between CONUT and clinical characteristics were estimated. Cox regression analyses with hazard ratios (HRs) and 95% confidence intervals (CIs) were also performed to evaluate the prognostic factors of DFS. Results Fifty-nine (27.3%) patients achieved pathologic complete response (pCR), and 30 (13.9%) cases had a recurrence. There were 150 cases (69.4%) in low CONUT group and 66 cases (30.6%) in high CONUT group, respectively. The results revealed that vessel invasion (P = 0.037), postoperative pneumonia (P = 0.001), advanced ypT stage (P = 0.011), cTNM stage (P = 0.007), and ypTNM stage (P < 0.001) were significantly related to patients with a high CONUT score. A high pCR rate was found in patients with a low CONUT score (33.3% vs. 13.6%, P = 0.003), and a high recurrence rate was found in patients with a high CONUT score (24.2% vs. 9.3%, P = 0.004), respectively. Patients with a low CONUT score had a better 1-year DFS than those with a high CONUT score (90.7% vs. 75.8%, P = 0.004). Multivariate analyses indicated that the pretreatment CONUT score was an independent predictor regarding DFS (HR = 2.221, 95% CI: 1.067–4.625, P = 0.033). Conclusion A better response and a lower recurrence were found in ESCC patients with a lower pretreatment CONUT. As a useful index for immune-nutritional status, the CONUT might be a reliable prognostic indicator in ESCC patients with nICT.